Morphology of Endothelial Cells from Different Regions of the Swine Cornea - Clerot, Lídia Luzia; Hünning, Paula Stieven; Bettio, Marcelle; Torikachvili, Marcela; Petersen, Michelle Beck; Silva, Alessandra Fernandez; Carissimi, Andre Silva; Pigatto, João Antonio Tadeu (Acta Scientiae Veterinariae, 2019)
Background: The corneal endothelium is a monolayer of polygonal cells which constitute the last layer of the cornea. The integrity of this layer is critical to cornea transparency. The characterization of normal corneal endothelial morphology is important not only to clinical evaluation but also to selection of areas of the cornea with better quality to be employed as donor tissue. The aim of the present study was to evaluate the morphology of endothelial cells from different regions of the swine cornea after alizarin red staining using optical microscopy. Materials, Methods & Results: Twenty-four healthy eyes from 12 swine Large White breed, with 14-month-old, males or females obtained from a licensed Brazilian commercial slaughterhouse were studied. Immediately after humane slaughter, the eyes were enucleated and submitted to ophthalmic examination. Eyes with signs of diseases of the anterior segment were excluded. The cornea, with 3 mm of the sclera, was removed and placed on a glass microscope slide with the endothelial side up. Four radial incisions were made in the periphery of the cornea to better accommodate the cornea on the microscope slide. Alizarin red was diluted in isotonic solution (0.2 g/100 mL) and the pH was adjusted to 4.2 with hydrochloric acid. Three drops of alizarin red were placed on the corneal endothelium. After 90 s, the dye was removed from the cornea with balanced saline solution. The corneal endothelium was examined and photographed using an optical microscope. All evaluations were performed by the same investigator. Photomicrographs were taken of central, superior, inferior, nasal and temporal corneal areas. Parameter studied included endothelial cell morphology. For the statistical analysis, was employed the ANOVA variance test (repeated measures). Differences were considered statistically significant at P < 0.05. Normal endothelium cells were mainly hexagonal (83.7%), pentagonal (7.45%) and heptagonal (8.8%), with a minimal number of cells of other shapes present. There were no significant statistical differences in the proportion of the morphology and the different regions of the cornea (P = 0.31). Discussion: Different techniques are available for the analysis of corneal endothelium, including mainly scanning electron microscopy, specular microscopy and optical microscopy. The analysis of the morphology of corneal endothelium with an optic microscope after staining with alizarin red has been described as an effective, rapid and cost-efficient method, since this dye blends the borated cells, allowing identification. In the present study, using optical microscopy and coloration with alizarin red it was possible to explore and to obtain images of the swine endothelium of all regions of the cornea. The analysis of the cellular morphology or the percentage of hexagonal cells are among the main parameters used to evaluate the health of the corneal endothelium. In this study, the endothelium had the predominance of the hexagonal shape in all regions studied. In swine, there are no studies evaluating the shape of the endothelial cells in the five different regions of the cornea. This study has demonstrated that the parameters evaluated in swine did not differ significantly between the various places of the cornea.